Implementation of Regional Tax Improvement Services in Calculating Bphtb Based on Land Value Zones E-BPHTB Application at the Regional Revenue Agency Office of Langkat Regency - Siregar, Lindha; Sinaga, Rudi Salam; Sihombing, Marlon (Journal of Public Representative and Society Provision, 2025)
Land Value Zone (ZNT) based on market value, ZNT can be used to determine tariffs in land services, community references in transactions, determining compensation, inventory of public and community asset values, monitoring land values ​​and land markets, and references for determining NJOP for PBB, to be fairer and more transparent. In the study, a ZNT map was formed based on land values ​​with mass assessments using a sales comparative approach which was overlaid with the Stabat District Administration Map, Langkat Regency and the 2013 PBB Block Map and compared with land values ​​based on NJOP. The land price data calculated is pure land price data with the value of buildings that have been issued and adjustments according to the characteristics of the Regional Socio-Economic conditions. The Results of the Study Obtained 49 Land Value Zones from NJOP (Taxable Object Sales Value) data and data based on the Land Price Transaction Survey. Meanwhile, from the analysis of the average increase in income, the increase in regional income based on the comparison between Transaction Price and NJOP Value was 409.31%.